Penentuan Nilai Premi pada Asuransi Pertanian Berbasis Indeks Iklim di Kabupaten Bogor - Ihfad Fahrur Roji (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Agriculture plays an important role in food security as well as a source of livelihood for millions of farmers with various types of agriculture. However, farmers often experience crop failure which results in losses. One of the causes of crop failure is flooding, especially in Bogor Regency which has the nickname